Determination of 105 antibiotic, anti-inflammatory, antiparasitic agents and tranquilizers by LC-MS/MS based on an acidic QuEChERS-like extraction. Issue 4 (3rd April 2018) - Desmarchelier, Aurélien; Fan, Kaïli; Minh Tien, Mai; Savoy, Marie-Claude; Tarres, Adrienne; Fuger, Denis; Goyon, Alexandre; Bessaire, Thomas; Mottier, Pascal
ABSTRACT: A procedure for screening 105 veterinary drugs in foods by liquid chromatography tandem mass-spectrometry (LC-MS/MS) is presented. Its scope encompasses raw materials of animal origin (milk, meat, fish, egg and fat) but also related processed ingredients and finished products commonly used and manufactured by food business operators. Due to the complexity of the matrices considered and to efficiently deal with losses during extraction and matrix effects during MS source ionisation, each sample was analysed twice, that is 'unspiked' and 'spiked at the screening target concentration' using a QuEChERS-like extraction. The entire procedure was validated according to the European Community Reference Laboratories Residues Guidelines. False-negative and false-positive rates were below 5% for all veterinary drugs whatever the food matrix. Effectiveness of the procedure was further demonstrated through participation to five proficiency tests and its ruggedness demonstrated in quality control operations by a second laboratory.